Pengembangan Bahan Ajar Video Animasi Berbasis Pendidikan Karakter pada Materi Sistem Persamaan Linier - Akhmad Yusup Efendi; Adisel Adisel; Fatrima Santri Syafri (Jurnal Pendidikan Matematika:Judika Education, 2022)
This study aims to determine the validity of the development and practicality of using animated video teaching materials based on character education for class VIII SMP/MTs on linear equation systems. This research is a research and development research and development (R & D) using a 4D model consisting of 4 stages, namely, Define, Design, Develop, Disseminate. Product trials were carried out in small groups of 14 students of class VIII and mathematics teachers. The results of the study where at the validation stage consisted of 4 validation people, namely 1 media expert, 1 character education value expert and 2 material experts with an average validation percentage of 82.94% with the "Very Valid" category. At the product trial stage to determine the practicality of using this mathematics module using a small group test (student responses) and the teacher's response obtaining an average score of 81.62% in the "Good" category. So it can be concluded that the development of animated video teaching materials based on character education for class VIII SMP/MTs on the linear equation system material that has been developed is valid and practical so that it is feasible to be used in the learning process. Keywords: Teaching Materials, Animated Videos, Character Education Values